Finite Element Modeling, Analysis and Fatigue Life Prediction of Lower Suspension Arm - M. M., Rahman; M. M., Noor; K., Kadirgama; R. A., Bakar; M. R. M., Rejab (2009)
This paper explores the finite element modeling, analysis and fatigue life prediction of lower suspension arm using the strain-life approach. Aluminum alloys are selected as a suspension arm materials. The structural model of the suspension arm was utilizing the Solid works. The finite element model and analysis were performed utilizing the finite element analysis code. TET10 mesh and maximum principal stress were considered in the linear static stress analysis and the critical location was considered at node(6017). From the fatigue analysis, Smith-Watson-Topper mean stress correction was conservative method when subjected to SAETRN loading, while Coffin-Manson model is applicable when subjected to SAESUS and SAEBRKT loading. From the material optimization, 7075-T6 aluminum alloy is suitable material of the suspension arm.